Evaluation of sanitation standard operating procedure (SSOP) implementation in nata de coco production process in micro-scale industry in Tempel, Sleman, Yogyakarta Special Region - Mefia, Amara Arta; Qathrunnada, Salwaa Khairunnisa; Esa, Sonia Dora Febri (Journal of Agritechnology and Food Processing, 2024)
The Standard Operational Sanitation System (SSOP) is a critical component in ensuring the safety of food products in the industry. Although SSOP has been implemented, many businesses still face challenges in effectively implementing it. Therefore, this study aims to analyze the SSOP in the small-scale UMKM (Micro, Small, and Medium Enterprises) coconut jelly industry and identify areas that require improvement. The study involved direct observations and interviews with relevant personnel, and the necessary data for analysis was collected. The findings of the research indicate that there are several weaknesses that require attention, including equipment maintenance deficiencies, personal hygiene, and inadequate cleaning procedures. This study underlines the importance of continuous monitoring and improvement in SSOP to enhance product safety and compliance with sanitation regulations. The research provides specific recommendations to address the identified shortcomings, including additional training for personnel and a review of cleaning procedures. We hope that these observations will provide valuable insights for other coconut jelly industries to improve the quality and safety of their products.